Drivers of Continued Surface Warming After Cessation of Carbon Emissions. Issue 20 (28th October 2017) - Williams, Richard G.; Roussenov, Vassil; Frölicher, Thomas L.; Goodwin, Philip
Abstract: The climate response after cessation of carbon emissions is examined here, exploiting a single equation connecting surface warming to cumulative carbon emissions. The multicentennial response to an idealized pulse of carbon is considered by diagnosing a 1, 000 year integration of an Earth system model (Geophysical Fluid Dynamics Laboratory ESM2M) and an ensemble of efficient Earth system model simulations. After emissions cease, surface temperature evolves according to (i) how much of the emitted carbon remains in the atmosphere and (ii) how much of the additional radiative forcing warms the surface rather than the ocean interior. The peak in surface temperature is delayed in time after carbon emissions cease through the decline in ocean heat uptake, which in turn increases the proportion of radiative forcing warming the surface. Eventually, after many centuries, surface temperature declines as the radiative forcing decreases through the excess atmospheric CO2 being taken up by the ocean and land. Key Points: Continued warming is explained using theory from a heat balance and a carbon inventory budget Peak global warming is delayed after the cessation of carbon emissions Timing of peak warming is controlled by the weakening of ocean heat uptake Plain Language Summary: The climate response after carbon emissions cease is examined here, exploiting a combination of theory and diagnostics of an Earth system model. The multicentennial response to an idealized pulse of carbon is considered over 1, 000 years. After emissions cease, surface temperature evolves according to (i) how much of the emitted carbon remains in the atmosphere and (ii) how much of the additional radiative forcing warms the surface rather than the ocean interior. Surface temperature continues to increase after carbon emissions cease through a decline in ocean heat uptake, which increases the proportion of radiative forcing warming the surface. Eventually, after many centuries, surface temperature declines as the excess atmospheric carbon dioxide is taken up by the ocean and land.